Mengulas Problematik Kegiatan Belajar-Mengajar di Tengah Pandemi: Reviewing Problematic Teaching and Learning Activities in the Middle of a Pandemic - Tinambunan, Hezron Sabar Rotua; Komariah, Mamay; Bakar, Dian Utami Mas (Fakultas Hukum Universitas Negeri Semarang, 2021)
The learning system that changed significantly during the Covid-19 pandemic had a major impact on the world of education. This learning change is a situation that requires entering information literacy in academic culture. One of the causes of this big change is because online learning is done suddenly, this has a big impact on the readiness of schools, teachers, and students in carrying out inadequate learning. In this condition, the law needs to be present to realize an effective online learning system, in addition to preparing cooperative learning methods. To answer this question, this research uses legal research methods. The right to education is the right of every citizen guaranteed in the constitution, or is a constitutional right of citizens. For the fulfillment of state education, it is necessary to establish standardization by being aware of the current condition of Indonesia. The government is obliged to prepare regulatory instruments for the implementation of education in accordance with the national goal of educating the nation's life. With adequate regulations, there will be legal protection for students to get proper learning even with online learning. In addition to adequate regulation, teachers in schools and parents at home and in the community have a vital role in the success of distance learning. Teachers and parents must provide or condition the best place for students to learn optimally.